2010
DOI: 10.1203/pdr.0b013e3181dc240f
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 Can Either Protect Against or Increase LPS-Induced Damage in the Developing Rat Brain

Abstract: Periventricular leukomalacia (PVL) is a major form of brain damage in premature infants. The present study was to test whether Insulin-like growth factor-1 (IGF-1) can prevent PVL-like brain damage induced by lipopolysaccharide (LPS) in the neonatal rat. Intraventricular delivery of LPS resulted in an acute brain inflammatory response, i.e., rapid recruitment of polymorphonuclear leukocytes (PMNs), activation of microglia and astrocytes, and induction of interleukin-1β (IL1β) expression. Brain inflammation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 25 publications
4
47
0
1
Order By: Relevance
“…33,34 However, the findings of a recent report suggest that IGF-1 could have beneficial as well as harmful effects on the developing brain. 35 This revelation supports the earlier observation that hyperactivated IGF-1 signaling shows accelerated aging and amyloid beta production in the brain. 36 Blockade of IGF-1 in nonexercising and exercising mice has revealed the complex role of IGF-1 in neurogenesis, dendritic spine density, CA1 pyramidal cells, and hippocampal structure.…”
Section: Introductionsupporting
confidence: 87%
“…33,34 However, the findings of a recent report suggest that IGF-1 could have beneficial as well as harmful effects on the developing brain. 35 This revelation supports the earlier observation that hyperactivated IGF-1 signaling shows accelerated aging and amyloid beta production in the brain. 36 Blockade of IGF-1 in nonexercising and exercising mice has revealed the complex role of IGF-1 in neurogenesis, dendritic spine density, CA1 pyramidal cells, and hippocampal structure.…”
Section: Introductionsupporting
confidence: 87%
“…Post-transcriptional control by microRNAs regulates OL differentiation and OPCs that lack mature microRNAs display arrested maturation (Dugas et al 2010; Shin et al 2009). Insulin-like growth factors (IGFs) promote OL lineage cell survival and myelination and protect against OL progenitor loss in fetal and neonatal models of WMI (Guan et al 2001; Pang et al 2010b; Wood et al 2007). Bone morphogenetic proteins both repress OL differentiation and regulate myelin protein expression (See et al 2004; See and Grinspan 2009).…”
Section: Cellular-molecular Mechanisms Of Acute Wmimentioning
confidence: 99%
“…Recently, Pang et al reported that IGF-I could have negative effects on the developing brain in an acute inflammatory condition [67]. On the one hand, a low dose of IGF-I prevented lipopolysaccharideinduced brain injury, but on the other hand the permeability of the blood-brain barrier was enhanced causing intracerebral hemorrhage.…”
Section: Discussionmentioning
confidence: 99%